Frilled Lizard Optimization to Optimize Parameters Proportional Integral Derivative of DC Motor - Widi Aribowo; Laith Abualigah; Diego Oliva; Toufik Mzili; Sabo Aliyu; Hisham A. Shehadeh (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
This paper presents a Proportional-Integral-Derivative (PID) parameter optimization method for direct current (dc) motors. The method utilizes a metaheuristic technique known as Frilled Lizard Optimization (FLO), which is inspired by natural processes. FLO draws inspiration from the lizard's hunting method of employing a sit-and-wait approach with great patience. The method is divided into two distinct phases: the exploration phase, which simulates a swift predator attack by a lizard, and the exploitation phase, which imitates the lizard's return to the treetop after feeding. This study confirms the effectiveness of FLO by conducting performance tests on the CEC2017 benchmark function and a DC motor. Through the simulations conducted on the CEC2017 benchmark function, it has been determined that FLO has superior exploration and exploitation capabilities. When testing a DC motor, it was discovered that the PID-FLO approach is effective in reducing overshoot and achieving optimal performance.